Coping utilized by adult stutterers, not in therapy (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The present paper intends to investigate, by using reports of people who stutter and who are not undergoing therapy for their stuttering, the coping (strategies) used to overcome their difficulties and face situations involving communication. The participants were three men and one woman, with ages varying between 31 and 54, stutterers since childhood, with no other history of neurological disease or brain damage. The interviews were recorded in audio, and speech samples of the participants, in situations of spontaneous conversation and reading, were recorded on video. These samples were utilized in evaluating the severity of the stuttering. Analysis of the results showed the participants acquired, throughout their lives, efficient ways to cope with their stuttering. Some of the coping (strategies) are used by all of the participants, such as rules, previous preparation of the subject of speech and stopping and starting. Many of the coping utilized by the participants can be found in specialized literature, in terms of efficiency.